2017
DOI: 10.1097/wnf.0000000000000252
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Loxapine for Agitation in Intoxicated Patients: A Case Series

Abstract: ObjectivesEpisodes of agitation are frequent in intoxicated patients who have a substance use disorder, a psychiatric disorder or both (dual diagnosis). For managing the agitation, it is necessary to act promptly in a safe environment and addressing any underlying etiology. Inhaled loxapine improves symptoms of agitation in adults with psychiatric disorders (eg, schizophrenia) within 10 minutes of administration. Recently, some reports have documented the usefulness of loxapine in dual diagnoses patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In a majority of studies reporting safety outcomes in patients with schizophrenia or BD, inhaled loxapine was well tolerated and did not produce excessive sedation [ 53 , 54 , 55 ]. The most commonly reported adverse effects were mild to moderate and included dysgeusia, throat soreness, and sedation [ 50 , 51 , 52 , 56 ].…”
Section: Pharmacological Managementmentioning
confidence: 99%
“…In a majority of studies reporting safety outcomes in patients with schizophrenia or BD, inhaled loxapine was well tolerated and did not produce excessive sedation [ 53 , 54 , 55 ]. The most commonly reported adverse effects were mild to moderate and included dysgeusia, throat soreness, and sedation [ 50 , 51 , 52 , 56 ].…”
Section: Pharmacological Managementmentioning
confidence: 99%
“…Key exclusion criteria of these studies were agitation primarily because of acute alcohol or drug intoxication/withdrawal and those considered to be at serious risk for suicide. Nevertheless, real-world evidence showed that acute agitation was effectively and quickly managed by inhaled loxapine in intoxicated patients in a retrospective review of data from a case series [ 42 , 43 ].…”
Section: Clinical Efficacy Of Inhaled Loxapinementioning
confidence: 99%
“…In approval studies, it was found superior to placebo with respect to the reduction of agitation in schizophrenia and bipolar disorder (NNT = 3, 95% CI [2; 4]) (8). Hardly any data are available on its safety in patients suffering from intoxication; in a case series with 12 patients that appeared too late to be considered for the aforementioned clinical practice guideline, the only adverse effect mentioned for this population was mild confusion (33). Loxapine is, however, still contraindicated for patients with airway diseases, because of the risk of bronchospasm.…”
Section: Loxapine Inhalationmentioning
confidence: 99%